Financial Programming and Policy : The Case of Hungary - Swiderski, Karen (Washington, D.C. : International Monetary Fund, 1992)
The case study of Hungary clarifies the specific macroeconomic policy requirements of countries in transition from centrally planned to market economies. The study, edited by Karen A. Swiderski, covers the period through 1990 and provides material needed to develop consistent projections of macroeconomic developments in Hungary.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet